Diagnostic accuracy of sarcopenia by "possible sarcopenia" premiered by the Asian Working Group for Sarcopenia 2019 definition. (November 2021) - Ueshima, Junko; Maeda, Keisuke; Shimizu, Akio; Inoue, Tatsuro; Murotani, Kenta; Mori, Naoharu; Satake, Shosuke; Matsui, Yasumoto; Arai, Hidenori
Highlights: Report of diagnostic accuracy of possible sarcopenia against sarcopenia by AWGS 2019. Diagnostic accuracy of possible sarcopenia for definitive sarcopenia is excellent. Definitive sarcopenia may be missed in case-finding with extremely reduced CC. Possible sarcopenia is appropriate for the detection of definitive sarcopenia. Abstract: Purpose: The Asian Working Group for Sarcopenia 2019 (AWGS 2019) proposed a simple assessment of sarcopenia called "possible sarcopenia" for the purpose of early detection and intervention of sarcopenia. The purpose of this study was to report the accuracy of possible sarcopenia against definitive sarcopenia and the characteristics of false-negative cases. Materials and Methods: This was a cross-sectional study using a research registry with outpatients aged ≥65 years who visited a frailty clinic at a geriatric hospital. The diagnosis of possible sarcopenia and sarcopenia was performed according to the AWGS 2019 criteria, using calf circumference (CC) for case-finding. The accuracy of the diagnosis of sarcopenia in participants with possible sarcopenia was evaluated by calculating sensitivity, specificity, and F-value. Results: Of the 349 patients (mean age, 78.0±6.0 years; 63% women) analyzed, 86 (24.6%) revealed possible sarcopenia. Possible sarcopenia predicted sarcopenia with a sensitivity of 0.893 and 0.921, specificity of 0.990 and 0.870, and F-values of 0.926 and 0.714 for men and women, respectively. When either the grip strength test or 5-time chair stand test result was examined, the sensitivity of possible sarcopenia to predict sarcopenia decreased, whereas the specificity remained at 0.990–1.000 in men and 0.890–0.940 in women. An extremely decreased CC was identified as a significant characteristic of patients with sarcopenia not detected in the simplified assessment. Conclusions: The diagnostic accuracy of possible sarcopenia for definitive sarcopenia is excellent. Sarcopenia should be actively examined in patients with extremely decreased CC.